Reasons Consumers Switch Products in the Era of Digital Abundance:: A Study of E-Commerce Behavior in the Border Region of North Kalimantan - Syahran Syahran; Ferawati Usman; Shalahuddin Shalahuddin; Zakaria Basran; Iqrima Mas Mappangile (Amkop Management Accounting Review (AMAR), 2026)
This study aims to examine the influence of price sensitivity, perceived variety abundance, and electronic word-of-mouth (eWOM) on consumer switching behavior in e-commerce platforms, with consumer trust in alternatives as a mediating variable. A quantitative approach with an explanatory design was used to analyze data from 300 active e-commerce user respondents in the North Kalimantan border region. Data processing was carried out using Structural Equation Modeling (SEM) techniques based on Partial Least Squares (PLS). The results of the analysis show that all exogenous variables have a significant influence on switching behavior, both directly and indirectly through consumer trust. Price sensitivity has the largest total influence on switching, followed by perceived variety abundance and eWOM. This study contributes to strengthening the Stimulus–Organism–Response (S-O-R) theory in the context of digital consumer behavior, specifically by positioning trust as a psychological mechanism that bridges the influence of the digital environment on switching decisions. These findings also have practical implications for e-commerce managers in designing pricing strategies, presenting product variations, and managing online reviews to build trust in alternative products and manage consumer loyalty more effectively in the era of high digital competition.